An Iterative Module in the Azalomycin F Polyketide Synthase Contains a Switchable Enoylreductase Domain. (18th April 2017) - Xu, Wei; Zhai, Guifa; Liu, Yuanzhen; Li, Yuan; Shi, Yanrong; Hong, Kui; Hong, Hui; Leadlay, Peter F.; Deng, Zixin; Sun, Yuhui
Abstract: Detailed analysis of the modular Type I polyketide synthase (PKS) involved in the biosynthesis of the marginolactone azalomycin F in mangrove Streptomyces sp. 211726 has shown that only nineteen extension modules are required to accomplish twenty cycles of polyketide chain elongation. Analysis of the products of a PKS mutant specifically inactivated in the dehydratase domain of extension‐module 1 showed that this module catalyzes two successive elongations with different outcomes. Strikingly, the enoylreductase domain of this module can apparently be "toggled" off and on : it functions in only the second of these two cycles. This novel mechanism expands our understanding of PKS assembly‐line catalysis and may explain examples of apparent non‐colinearity in other modular PKS systems.